2013
DOI: 10.1021/es304944c
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics and Metabolites of Carbamazepine in Soil

Abstract: The antiepileptic drug carbamazepine (CBZ) is one of the most frequently detected human pharmaceuticals in wastewater effluents and biosolids. Soil is a primary environmental compartment receiving CBZ through wastewater irrigation and biosolid application. In this study, we explored the transformation of CBZ to biologically active intermediates in soil. Both (14)C labeling and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were used to track transformation kinetics and identify major degradation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 34 publications
3
97
0
1
Order By: Relevance
“…This result is consistent with greater recalcitrance of CBZ to biodegradation. Carbamazepine was reported to be dissipated only very slowly in three different soils with the half-life ranging from 46 to 173 days (Li et al, 2013). In this study, over a 120-day laboratory incubation with only negligible amounts of 14 C-CBZ were mineralized or formed non-extractable residues, recovery of 14 C in the form of extractable parent and various transformation products was almost stoichiometric.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This result is consistent with greater recalcitrance of CBZ to biodegradation. Carbamazepine was reported to be dissipated only very slowly in three different soils with the half-life ranging from 46 to 173 days (Li et al, 2013). In this study, over a 120-day laboratory incubation with only negligible amounts of 14 C-CBZ were mineralized or formed non-extractable residues, recovery of 14 C in the form of extractable parent and various transformation products was almost stoichiometric.…”
Section: Discussionmentioning
confidence: 54%
“…In Canada, an estimated 53-62 tons are sold annually (McLaughlin and Belknap, 2008). Based on previous experience, we anticipated that CBZ would be persistent, and NAP rapidly dissipated in soil under permissive conditions (Li et al, 2013;Topp et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…14 C-naproxen and 14 C-diclofenac were found to be mainly (up to 50-80%) mineralized to 14 CO 2 in different soils (Dodgen et al, 2014;Topp et al, 2008), while only a small part of 14 C-carbamazepine (b1.2%) and 14 C-acetaminophen (17%) were mineralized . Some metabolites of pharmaceuticals in soils were identified by using a combination of techniques, including 14 C labeling, LC fractionation, and LC-MS/MS structural elucidation (Dodgen et al, 2014;Li et al, 2013Li et al, , 2014. It was reported that acetaminophen was rapidly converted to various metabolites in soils , while slow and limited transformation was observed for carbamazepine .…”
Section: Fate Of Ppcps In Soilmentioning
confidence: 99%
“…It was reported that irrigation with treated wastewater had no discernable effect on the biodegradation of PPCPs in soil (Grossberger et al, 2014), whereas biosolids amendment generally inhibited the degradation of PPCPs (Monteiro and Boxall, 2009;Li et al, 2013Li et al, , 2014, therefore prolonging their persistence in soil. The reason for this inhibition of degradation may be that biosolids amendment usually increases the organic matter content in soil, leading to increased sorption of PPCPs to soil (and hence decreased bioavailability) .…”
Section: Factors Affecting the Degradation Of Ppcps In Soilmentioning
confidence: 99%
“…This is most likely caused by the fact that carbamazepine forms a range of degradation intermediates in soil which further reduce the amount of parent compound (Li et al 2013). Additionally, relatively small amount of carbamazepine is annually used in Finland (3200 kg), and therefore, small concentrations are released from the WWTP (Table 1).…”
Section: Sedimented Particlesmentioning
confidence: 99%